Desenvolvimento de método analítico com emprego da espectrometria de absorção atômica para a determinação de Cd, Fe, Pb e Zn em amostras de interesse alimentício - Col, José Augusto da (2008)
Analytical chemistry plays a fundamental role in proposing fast and reliable procedures to analyze food samples. Proper selection and introduction of complementary foods reduces the vulnerability to micronutrient deficiencies. This study aimed to propose a sensitive approach for the promotion of adequate food supplements regarding Cd, Fe, Pb and Zn contents. For the development of this method, factorial design was used for experimental conditions optimization. These metals were determined using Flame Atomic Absorption Spectrometry - FAAS (Fe and Zn) and Thermospray Flame Furnace AAS (Cd and Pb). In TS-FF-AAS, a nickel tube is used as atomizer; since the sample is totally introduced into the tube, an increase in method sensitivity is obtained. Besides, flame residence time is extended, increasing efficiency of atomizing processes. Additionally, a simple procedure mixing the sample (100 mg) with 0.1 mol/L HCl was proposed. In food analysis, limits of detection (LOD) of 0.6, 100, 6.0 and 32 µg/L for Cd, Fe, Pb and Zn were obtained, respectively. Standard Relative Deviations (RSD) for elements Cd (n = 14), Fe (n = 3) and Zn (n = 19) were of 7.0, 5.5 and 6.0%, respectively. Analytical frequency of the method was of 28 determinations per hour with an analytical speed of 8 samples per hour (from sample preparation to determination). All determinations were performed with the same atomizing tube, which, even after 2270 determinations (around 76 h), did not present sensitivity losses. Cadmium and Zn showed suitable results when a bovine liver certified sample (SRM 1577b) was studied and the Fe content was strongly correlated to the size of the particle. Toxic metals Cd and Pb were not detected in the studied food samples. Regarding the essential elements, there was no increase in the Fe and Zn when the supplement is used. Information about food quality could be obtained, and the proposed method fits the purpose.